Getting started with Dreamweaver CC - Blake, Geoff (Ten Ton Books, 2015)
"Delve into the world of web design and Dreamweaver with this hands-on, step-by-step course hosted by award-winning software trainer and designer, Geoff Blake. First, Geoff will run you through the basics, getting you comfortable in the Dreamweaver interface, working with documents, and defining new websites. Then, it's on to building a fully functional web layout from the ground up. You'll learn how to construct your design, insert navigation menus, and test your work for usability. Handling text, graphics, and setting up a well-built set of site-wide CSS rules to control it all brings your site together; and Geoff even takes you through the process of rolling out your website, and taking your site live by uploading it to a live web server. Roll up your sleeves and delve into this practical, task-oriented look at building contemporary websites in Dreamweaver CC!"--Resource description page.